2013
DOI: 10.1177/0081246313484238
|View full text |Cite
|
Sign up to set email alerts
|

Wellness without fairness: The missing link in psychology

Abstract: To promote human welfare, psychologists must advance two important goals: wellness and fairness. Hitherto, research on wellness or well-being has discovered connections among overall satisfaction with life and important facets of life, such as relationships, income, and physical health, but the connections among various types of wellness and specific aspects of fairness remain obscure. Research on justice in psychology, in turn, has focused largely on the impact of distributive, procedural, and interactional j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 50 publications
0
29
0
1
Order By: Relevance
“…This idea captures a simple way of understanding social justice as applied to counselling and psychotherapy. Firstly, though we are doing something very personal, often working with people at individual or small group levels, considering issues relating to the individual or small group, these issues are so intertwined with our broader social and political environments that they are very hard to disentangle or separate (Prilleltensky, ). Secondly, our work can have a political function if it challenges traditionally unequal structures and facilitates new power relations.…”
Section: What Is Social Justice?mentioning
confidence: 99%
“…This idea captures a simple way of understanding social justice as applied to counselling and psychotherapy. Firstly, though we are doing something very personal, often working with people at individual or small group levels, considering issues relating to the individual or small group, these issues are so intertwined with our broader social and political environments that they are very hard to disentangle or separate (Prilleltensky, ). Secondly, our work can have a political function if it challenges traditionally unequal structures and facilitates new power relations.…”
Section: What Is Social Justice?mentioning
confidence: 99%
“…Latin American CP draws on liberation theology (Lowy, 1996), whereas South Afri can CP has also been influenced by Black thought and consciousness, including the ideas of Frantz Fanon and Steve Biko (1946-1977see Hook, 2004). North American CP draws on moral positions (Prilleltensky, 2013;Tolman, 2001) challenging social injustices in areas such as gender, race, immigration, poverty, and sexual preference (e.g., Fine, 2012;Nelson, 2013;Prilleltensky & Nelson, 2013;Sweeney & Opotow, 2013). Considering the North American usage of the word, the term critical may include connections with critical race theory, critical dis ability studies, critical pedagogy, queer studies, feminist standpoint theory, some postmodern theories, or with the project of antipsychiatry.…”
Section: T H E O R E T I C a L R O O Tsmentioning
confidence: 99%
“…Lupton (2014) has argued that 'The key point, of course […] is that the problem of educational inequalities is caused by society, not by schools' (p. 922) and 'Teachers on their own cannot make all the difference, although they can certainly make a difference' (p. 923). Critical psychologists have long argued that individual psychologists treating psychological distress within the individual is at best misguided, given the role of social and political factors in influencing well-being (Prilleltensky, 2013). Similarly, it should be acknowledged that schools cannot address on their own the link between poverty and education, given the significant role of broader social policies.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, however, has been critiqued by 'critical psychology', as underestimating the impact of the social context on the individual, and ignoring the political nature of psychology (Parker, 2007;Prilleltensky and Fox, 1997). There is no single 'critical psychology' (Dafermos et al, 2013;Teo, 2015); critical psychologists have argued that psychological discourse should consider not only wellness, but also fairness or justice, given the evidence demonstrating the significant interrelationships between wellness and fairness (Prilleltensky, 2013). Research focusing on the 'social determinants of health' has found that mental health problems are strongly associated with multiple social, economic and political factors: 'People are made vulnerable to mental ill-health by deeprooted poverty, social inequality, and discrimination' (Allen et al, 2014, p. 402).…”
Section: A Critical Psychology Perspective On Education Andmentioning
confidence: 99%